Seasonality of medically attended norovirus gastroenteritis and its association with climatic factors within an US integrated healthcare system, 2016–2019 - Claire P. Mattison; Laura E. Calderwood; Jordan E. Cates; Judy Donald; Aron J. Hall; Mark A. Schmidt; Sara A. Mirza (PLoS ONE, 2025)
Background While acute gastroenteritis (AGE) occurs year-round, norovirus has a winter seasonality in the United States. Objective We analyzed norovirus seasonality within a US integrated healthcare delivery system from 2016–2019. Methods Electronic medical records were collected for acute gastroenteritis (AGE) encounters with specific ICD-9/10 codes or clinical stool testing. Norovirus percent positivity was calculated as the 8-week centered rolling average. Temperature and absolute humidity data were measured via weather station. The relationship between these factors and weekly norovirus episodes were modeled via negative binomial models. Results From 2016–2019, there were 198,181 AGE episodes reported; among the 18,998 episodes tested, 892 (5%) were norovirus positive. Norovirus percent positivity peaked in epidemiologic week 7 at 9%. Two negative binomial models showed significant inverse relationships between weekly number of norovirus episodes and both temperature and absolute humidity. Conclusion Norovirus AGE exhibited winter seasonality from 2016–2019, associated with lower temperatures and humidity. Understanding this seasonality may help predict peak transmission periods and their impact on healthcare resources.